TREATMENT AND DIAGNOSIS OF DUODENAL ULCER DISEASE IN CHILDREN - KHALILOV Sh.K. (Scholar Express Journals, 2025)
Duodenal ulcer disease in children is an urgent problem of modern pediatrics, characterized by a steady increase in morbidity and rejuvenation of the patient population. According to epidemiological studies, the prevalence of this pathology in the pediatric population varies from 1.7 to 16%, and there is a tendency to increase the frequency of severe and complicated forms of the disease. The peculiarities of the pediatric organism, atypicality of the clinical picture and multifactorial pathogenesis create significant difficulties in timely diagnosis and the choice of optimal treatment tactics. Despite the successes achieved in the study of etiopathogenesis and the development of therapeutic methods, the frequency of disease recurrence remains high, which determines the need for further improvement of diagnostic and therapeutic approaches
Keywords: duodenal ulcer disease; erosive gastroduodenitis